Assessment of seismic collapse probability of RC shaft supported tank. (October 2021) - Amin, Jignesh; Gondaliya, Kaushik; Mulchandani, Chirag
Abstract: The present study investigates the response reduction factor and seismic vulnerability of reinforced concrete shaft supported elevated tanks. Twenty-one prototypes of elevated tanks covering wide range of distinct sizes and heights are designed using appropriate Indian codes. The pushover analysis of finite element models is carried out to obtain the response reduction factor from the approximated bilinear pushover curve. The outcome of study shows that the tank capacity and shaft height are critical parameters influencing response reduction factor and its components. Hence, it is advised not to use the code specified unique values of response reduction factor for all tanks, regardless of their size and height for their desired seismic performance. The seismic vulnerability of the shaft stagging corresponding to various damage states has been also evaluated. The increase in the size of the tank reduces its lateral deformation capacity but increases the seismic fragility compared to tanks of smaller size. The probability of undergoing complete damage for seismic hazard corresponding to design basic and maximum considered earthquake level for code-conforming tanks is found to be less than 10%, and 30% respectively. The tanks of large sizes designed in conformity with standards are observed more susceptible to seismic forces compared to tanks of small and medium sizes.